2020
DOI: 10.3390/molecules25184256
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Light Intensity, Temperature, and Nutrients to Enhance the Bioactive Content of Hyperforin and Rutin in St. John’s Wort

Abstract: St. John’s wort (Hypericum perforatum L.) is a medicinal plant that alleviates depression and other disorders due to its abundance of active ingredients. Hyperforin, rutin, and melatonin are the main active, and important, ingredients in St. John’s wort that alleviate depression. In order to investigate the optimal conditions for accumulating these active ingredients, design of experiments and response surface methodology (RSM) was employed in this study. Two-month-old St John’s wort plants were cultivated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…Yesaghi (2006) studied three habitats in Iran and determined that carbon and N-rich soil provided more suitable conditions for the vegetative growth of H. perforatum. Kuo et al (2020) and Mir al. (2019) reported a positive correlation between hyperforin content and soil organic carbon and N. Furthermore, the increasing altitude from 1400 to 2800 m led to an increase in hyperforin content from 24 to 27 mg/g, respectively,…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Yesaghi (2006) studied three habitats in Iran and determined that carbon and N-rich soil provided more suitable conditions for the vegetative growth of H. perforatum. Kuo et al (2020) and Mir al. (2019) reported a positive correlation between hyperforin content and soil organic carbon and N. Furthermore, the increasing altitude from 1400 to 2800 m led to an increase in hyperforin content from 24 to 27 mg/g, respectively,…”
Section: Discussionmentioning
confidence: 95%
“…Yesaghi ( 2006 ) studied three habitats in Iran and determined that carbon and N‐rich soil provided more suitable conditions for the vegetative growth of H. perforatum . Kuo et al ( 2020 ) and Mir et al ( 2019 ) reported a positive correlation between hyperforin content and soil organic carbon and N. Furthermore, the increasing altitude from 1400 to 2800 m led to an increase in hyperforin content from 24 to 27 mg/g, respectively, which is inconsistent with the results of Walker et al ( 2001 ), Kleemann et al ( 2014 ) and Xenophontos et al ( 2008 ) who understood there wasn't any significant difference in amount of hyperforin and hypericin in different altitudes. Altitude is well known factor that can significantly impact secondary metabolism and cause variation in quality and quantity of major essential oil components of H. perforatum (Seyis et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, hyperforin, hypericin, pseudohypericin, and flavonoids are the principal components of H. perforatum extracts and are considered to be responsible for the extractsʼ pharmacological effects [20,98]. In fact, these authors specifically cite hyperforin and rutin as the main active ingredients in St. Johnʼs wort that reduce depressive symptoms; however, other authors also described melatonin as a principal component in this species [99]. As frequently occurs in phytotherapy, the synergy between constituents is a vital aspect of efficacy, as evidenced by the fact that the absence of rutin, a common flavonoid, reduces the antidepressant activity [20] while low hyperforin content preparations are effective in the treatment of depression [98].…”
Section: Hypericum Perforatum L (Hypericaceae)mentioning
confidence: 99%